High performance cobalt-free perovskite cathode for intermediate temperature solid oxide fuel cells - Niu, Y.; Zhou, W.; Sunarso, J.; Ge, L.; Zhu, Z.; Shao, Zongping (The Royal Society of Chemistry, 2010)
Bi doping of SrFeO3-d results in the formation of a structure with high symmetry and extraordinary electrochemical performance for Bi0.5Sr0.5FeO3-d, which is capable of competing effectively with the current Co-based cathode benchmark with additional advantages of lower thermal expansion and cost. © 2010 The Royal Society of Chemistry.